2022
DOI: 10.1002/smll.202107182
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Nanoarchitectured SERS Substrates: Nanospaces, 2D Materials, and Organic Heterostructures

Abstract: This article reviews recent fabrication methods for surface‐enhanced Raman spectroscopy (SERS) substrates with a focus on advanced nanoarchitecture based on noble metals with special nanospaces (round tips, gaps, and porous spaces), nanolayered 2D materials, including hybridization with metallic nanostructures (NSs), and the contemporary repertoire of nanoarchitecturing with organic molecules. The use of SERS for multidisciplinary applications has been extensively investigated because the considerably enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 315 publications
0
61
0
Order By: Relevance
“…It may be a promising strategy to design two-dimensional substrate materials at the nanometer level by using chemical and physical fabrication methods and composite them with traditional precious metals. 109,110 More innovation in the preparation methods of substrate materials is desired, and the continuous look for potential SERS substrate materials is highly demanded.…”
Section: Summary and Prospectivementioning
confidence: 99%
“…It may be a promising strategy to design two-dimensional substrate materials at the nanometer level by using chemical and physical fabrication methods and composite them with traditional precious metals. 109,110 More innovation in the preparation methods of substrate materials is desired, and the continuous look for potential SERS substrate materials is highly demanded.…”
Section: Summary and Prospectivementioning
confidence: 99%
“…SERS is an emerging spectroscopic detection technology with the advantages of rapidity, ultra-high sensitivity, and portability of equipment. 7,8 The application prospects of SERS in many fields, such as biomedical research, food safety, and drug detection, have been fully confirmed in recent decades. [9][10][11] The peak at each Raman frequency shift position in the SERS spectrum corresponds to a vibrational or rotational mode of a molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the abovementioned methods, surface-enhanced Raman spectroscopy (SERS), as an analytical tool, features ultrahigh sensitivity and the possibility of recognizing the chemical structures of target analytes with quantitative resolution. , SERS substrates are mainly fabricated with noble metals (Ag, Au, and Cu) due to their strong interaction with electromagnetic waves and the excitation of the localized surface plasmon resonance . Going beyond a single noble metal plasmonic structure, bimetallic plasmonic systems mainly presented by Au + Ag are rapidly growing since their hybrid nature is highly appealing for SERS sensing. , This appeal is explained by the combination of the enhanced plasmonic properties (high extinction coefficient) of Ag and the chemical stability of Au in one structure.…”
Section: Introductionmentioning
confidence: 99%